Economic evaluation of shortened, bedaquiline-containing treatment regimens for rifampicin-resistant tuberculosis (STREAM stage 2): a within-trial analysis of a randomised controlled trial. Issue 2 (February 2023) - Rosu, Laura; Madan, Jason J; Tomeny, Ewan M; Muniyandi, Malaisamy; Nidoi, Jasper; Girma, Mamo; Vilc, Valentina; Bindroo, Priyanka; Dhandhukiya, Rajdeep; Bayissa, Adamu K; Meressa, Daniel; Narendran, Gopalan; et al.
Summary: Background: The STREAM stage 2 trial assessed two bedaquiline-containing regimens for rifampicin-resistant tuberculosis: a 9-month all-oral regimen and a 6-month regimen containing an injectable drug for the first 2 months. We did a within-trial economic evaluation of these regimens. Methods: STREAM stage 2 was an international, phase 3, non-inferiority randomised trial in which participants with rifampicin-resistant tuberculosis were randomly assigned (1:2:2:2) to the 2011 WHO regimen (terminated early), a 9-month injectable-containing regimen (control regimen), a 9-month all-oral regimen with bedaquiline (oral regimen), or a 6-month regimen with bedaquiline and an injectable for the first 2 months (6-month regimen). We prospectively collected direct and indirect costs and health-related quality of life data from trial participants until week 76 of follow-up. Cost-effectiveness of the oral and 6-month regimens versus control was estimated in four countries (oral regimen) and two countries (6-month regimen), using health-related quality of life for cost-utility analysis and trial efficacy for cost-effectiveness analysis. This trial is registered with ISRCTN, ISRCTN18148631. Findings: 300 participants were included in the economic analyses (Ethiopia, 61; India, 142; Moldova, 51; Uganda, 46). In the cost-utility analysis, the oral regimen was not cost-effective in Ethiopia, India, Moldova, and Uganda from either a provider or societal perspective. In Moldova, the oral regimen was dominant from a societal perspective. In the cost-effectiveness analysis, the oral regimen was likely to be cost-effective from a provider perspective at willingness-to-pay thresholds per additional favourable outcome of more than US$4500 in Ethiopia, $1900 in India, $3950 in Moldova, and $7900 in Uganda, and from a societal perspective at thresholds of more than $15 900 in Ethiopia, $3150 in India, and $4350 in Uganda, while in Moldova the oral regimen was dominant. In Ethiopia and India, the 6-month regimen would cost tuberculosis programmes and participants less than the control regimen and was highly likely to be cost-effective in both cost-utility analysis and cost-effectiveness analysis. Reducing the bedaquiline price from $1·81 to $1·00 per tablet made the oral regimen cost-effective in the provider-perspective cost-utility analysis in India and Moldova and dominate over the control regimen in the provider-perspective cost-effectiveness analysis in India. Interpretation: At current costs, the oral bedaquiline-containing regimen for rifampicin-resistant tuberculosis is unlikely to be cost-effective in many low-income and middle-income countries. The 6-month regimen represents a cost-effective alternative if injectable use for 2 months is acceptable. Funding: USAID and Janssen Research & Development.